1337 A Regional Review of The Epidemiology and Pathological Characteristics of Malignant Melanoma in Northern Ireland (NI), And Correlation with Socio-Economic Status. (12th October 2021) - Currie, R; Martin, S; McAllister, S
Abstract: Introduction: The incidence of cutaneous malignant melanoma is increasing. Internationally, there is evidence of an association between melanoma incidence and higher socioeconomic status (SES). This study aims to assess the characteristics of patients with melanoma in NI, and correlate to SES. Method: Retrospective review of electronic records for patients undergoing surgery for melanoma at the Northern Ireland Plastic Surgery Unit from August 2015 to March 2020. Patients were identified from theatre records and a prospectively collected sentinel lymph node database. The NI Multiple Deprivation Measure 2017 was used to measure SES. Results: 440 patients were included (F = 54%, M = 46%). Mean age=63 (M = 67, F = 59). Mean Breslow Depth (BD) = 2.61mm (Range 0.17 – 27mm). Females had significantly thinner tumours at presentation (mean BD 2.16mm. vs 3.1mm in males, p = 0.001). In males the commonest sites were head and neck (36%) and back (23%). In females, the commonest sites were lower limb (42%) and upper limb (23%). There was a positive correlation between higher SES and increased incidence of melanoma (correlation coefficient (CC) 0.922), but this did not correlate with an increase in Breslow depth (CC -0.020). Conclusions: This study provides important information on melanoma in NI, including gender and site variances. Females were more commonly affected and were a mean of 8 years younger than males at diagnosis but presented with significantly thinner tumours. Unlike the rest of the UK, the commonest site in males was the head and neck. Higher SES was related to higher incidence of melanoma but with presentation at an earlier stage of disease.